Evaluating the coefficient of consolidation using penetration tests. Issue 3 (September 2001) - House, A.R.; Oliveira, J.R.M.S.; Randolph, M.F.
Abstract : This paper discusses the potential for using variable rate penetration tests as a means of assessing the consolidation coefficient for fine-grained soils. Previous testing has shown that the penetration resistance increases as the rate of penetration decreases, owing to partial consolidation in the soil ahead of the advancing probe. This led to the idea of reducing the penetration rate over a short interval during a standard (rapid) test, in order to identify the velocity at which consolidation effects become significant. By matching that point against a normalised backbone curve of penetration resistance versus non-dimensionalised velocity, the consolidation coefficient, cv, of the soil may be deduced. To explore this idea, a series of penetration tests in kaolin clay were undertaken on a drum centrifuge at the University of Western Australia (UWA), using a cylindrical T-bar penetrometer. A backbone curve was first established using constant penetration rate tests, but with velocities covering nearly 3 orders of magnitude. Then, a series of 'twitch' tests were undertaken, where the velocity was successively halved over 8 steps, from a high value (corresponding to undrained conditions) down to 0.4% of the initial value, with the penetrometer being advanced by either 1 or 2 diameters in each step. Comparison of the normalised penetration resistance with the backbone curve provided an estimate of the coefficient of consolidation, which was compared with independent estimates from oedometer tests. The tests gave very encouraging results, with the potential for the value of cv to be estimated within an error band of ±20%.